2017
DOI: 10.1155/2017/4818537
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Melanoma to the Urinary Bladder of Ocular Origin Accompanied with Primary Cutaneous Melanoma: Diagnostic Challenge—A Report of a Case

Abstract: Metastases of melanoma to the urinary bladder are infrequent. Even rarer are metastases to the urinary bladder from uveal melanoma, with only 3 cases published in the literature so far. Herein we present a case of a 77-year-old male patient who presented with metastatic melanoma to the urinary bladder. The patient's history included the diagnoses of uveal melanoma treated with radiation 25 years ago, as well as that of cutaneous melanoma diagnosed 7 years ago. The molecular study of the urinary bladder tumor s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…However, close study and reconstruction of the clinical history demonstrated that 15 years before, the woman had undergone enucleation of the left ocular bulb for primary ocular MM. This case was, therefore, the third report in literature of this very rare occurrence [45,46]. In light of the results of this review of MM of the urinary bladder, we can state that we believe the above-mentioned criteria for the kidney, proposed by Ainsworth et al, remain valid today.…”
Section: Urinary Bladdermentioning
confidence: 52%
See 2 more Smart Citations
“…However, close study and reconstruction of the clinical history demonstrated that 15 years before, the woman had undergone enucleation of the left ocular bulb for primary ocular MM. This case was, therefore, the third report in literature of this very rare occurrence [45,46]. In light of the results of this review of MM of the urinary bladder, we can state that we believe the above-mentioned criteria for the kidney, proposed by Ainsworth et al, remain valid today.…”
Section: Urinary Bladdermentioning
confidence: 52%
“…et al [31] 2011 [39] 2021 Primary CH and adjuvant CHT 16 months Maeda, T. et al [40] 2008 Metastatic CH, CHT and IT some months Nohara, T. et al [41] 2009 Metastatic TURBT and CHT some months Siroy, A.E. et al [42] 2011 Primary TURBT and CH some months Efesoy, O. et al [43] 2011 Metastatic TURBT and CHT 7 months Meunier, R. et al [44] 2015 Metastatic TURBT, CH and CHT some months Theocharides, C. et al [45] 2017 Metastatic TURBT and IT some months Paterson, A. et al [46] 2012 Metastatic CH and CHT <5 months Ikeda, A. et al [47] 2013 Metastatic TURBT and CHT <5 months Topal, C.S. et al [48] 2016 Among these, 9 patients had primary/metastatic MM of the kidney and 7 patients primary/metastastic MM of the ureter, 43 patients had primary/metastatic MM of the bladder and 88 patients primary/metastatic MM of the urethra (males and females).…”
Section: Author(s) Year(s) Primary/metastatic Treatment Survivalmentioning
confidence: 99%
See 1 more Smart Citation
“… 3 The authors of this article found only six cases of metastasized choroid melanoma to the bladder. 4 Patients with metastases localized to the bladder and good performance status may benefit from radical cystectomy, although the overall maximum reported survival was of 3 years. The role of traditional chemotherapy in metastatic melanoma is limited, as little survival benefit is achieved, currently, first line chemotherapy involves the use of alkalizing agents such as.…”
Section: Discussionmentioning
confidence: 99%
“…It has a bad prognosis. <30 cases of metastatic melanoma to the bladder have been reported in the English literature to date; 5 of these cases were recognized, and 62 reported cases were combined to create the literature study [ [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] ]. The presented case is the 63rd.…”
Section: Introductionmentioning
confidence: 99%